Rancang Bangun Sistem Monitoring Akademik Program Studi Teknik Informatika Universitas Mataram Menggunakan Data Warehouse - I Wayan Agus Arimbawa; Ni Ketut Dewi Febri Wantari; Ario Yudo Husodo (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
Informatics Engineering Department (PSTI) is one of the study program in University of Mataram which was established in 2012. PSTI has Academic Information System (AIS) which is used for supporting academic operational activities. However, AIS has not been able to provide any information or special report for chairman and secretary of PSTI. According to the interview with the chairman of PSTI, PSTI’s information needs are not only consisted of accreditation information but also non accreditation information. The needs for accreditation information that is apllied referring to the 3,4, and 5 standard in National Accreditation Board for Higher Education Book VI. The aim of this system is to help PSTI in providing such information so that the chairman and the secretary can identify the problem of PSTI fastly and accurately. The system is built with Laravel Framework as PHP and JavaScript as its language, and it uses Application Programing Interface (API) in order to integrate it with SIA. Moreover, it uses also data warehouse as an integrated storage. This system was developed using waterfall development method. When the system was tasted using black box method, all the function ran well, and the accuration testing showed that this system has resulted an output that corespond with the calculations performed manually. Therefore, it can be concluded that this system is ready to be used.